Comprehensive Midwifery Care for Mrs. S with the Application of Back Massage at Puskesmas Johan Pahlawan - Tiara Fernanda; Fitra Ermila Basri; Nanda Norisa; Satrinawati Satrinawati; Evi Zahara (Oshada, 2024)
A mother who has children has breastfeeding problems with a lack of knowledge because she is busy taking care of other children. One of the actions that midwives can take to help maximize breast milk production by increasing the hormone oxytocin in the body. In postpartum mothers. The purpose of this report is to implement comprehensive midwifery care management according to midwifery care standards with the application of back massage during the postpartum period. This report uses the case report method with primary and secondary data collection techniques. Comprehensive obstetric care is provided to Mrs. S starting from 38 weeks of pregnancy, childbirth, postpartum, family planning, neonates and babies at the Johan Pahlawan Health Center in West Aceh Regency from July 22 to September 2, 2024. During pregnancy, it was found that the problem of discomfort was often BAK, after an assessment was carried out that the problem faced by Mrs. S was physiological because there was an emphasis on the bladder and the head had begun to go down under the pelvis. During childbirth, it is normal and there are no complications or complications. In postpartum care, back injection is carried out to facilitate breast milk. Newborn care was not found to be a problem, the baby had received HBO, BCG and polio immunizations and family planning care was given sterile care. Comprehensive midwifery care has an impact on improving maternal and infant health, so it is important to do it in every care. The application of back massage carried out during the postpartum period can provide benefits to breast milk production.